Specification language quality evaluation procedure - Gasperovič, Jelena (Lietuvos matematikos rinkinys, 2004)
The paper describes quality evaluation procedure and gives example of its application. The purpose of the paper is to propose a way to determine specification language appropriateness for concrete project.
Keywords: quality model; quality characteristics; quality in use; evaluation procedure; fuzzy function